Tip convolution on HOPG surfaces measured in AM-AFM and interpreted using a combined experimental and simulation approach. (2nd December 2016) - Hu, Xiaoli; Chan, Nicholas; Martini, Ashlie; Egberts, Philip
Abstract: Amplitude modulated atomic force microscopy (AM-AFM) was used to examine the influence of the size of the AFM tip apex on the measured surface topography of single highly oriented pyrolytic graphite (HOPG) atomic steps. Experimental measurements were complemented by molecular dynamics simulations of AM-AFM and the results from both were evaluated by comparison of the measured or simulated width of the topography at the step to that predicted using simple rigid-body geometry. The results showed that the step width, which is a reflection of the resolution of the measurement, increased with tip size, as expected, but also that the difference between the measured/simulated step width and the geometric calculation was tip size dependent. The simulations suggested that this may be due to the deformation of the bodies and the effect of that deformation on the interaction force and oscillation amplitude. Overall, this study showed that the resolution of AM-AFM measurements of atomic steps can be correlated to tip size and that this relationship is affected by the deformation of the system.